The Rule of Law for the Government Authority of the Cabinet - Soontornsaratoon, Patcharawadee (Journal of Humanities and Social Sciences Uttaradit Rajabhat University, 2023)
The objective of the research was to formulate a law to apply the rule of law to the use of governmental powers of the Cabinet. The research used qualitative research methodology, including document research. in-depth interview, participation in design, co-design and feedback to collect and analyze information. The results showed that the use of governmental powers by the Cabinet is essential for direction and development of the country and affect the well-being of the people. At present, the Constitution of the Kingdom of Thailand, B.E. 2560 (2017) contains provisions for the Cabinet to adopt the rule of law in the administration of the country. There is a provision for the Cabinet to bring the rule of law to be used in the administration of the country. But the problem is that there has been no study and research on the rule of law suitable for exercising the governmental powers of the Cabinet. The results of this research have therefore been answered in the rule of law that is suitable for the Cabinet to apply. And in order for the rule of law to be implemented in a concrete manner, there must be a law to support it by applying good governance as a mechanism for clearer use of the rule of law, which research requires the development of the State Administration Act B.E. 2534 (2000) by adding a true rule of law which is the principles of equality and good governance that the Council of Ministers must consider are complementary to more effective enforcement, such as public participation, principles of transparency and accountability, the principle of value for money, etc., with the structure of the additional provisions, which is to specify that the use of government powers of the Cabinet must have the rule of law by taking the principles of good governance into account, which will enforce the rule of law and the use of government powers of the Cabinet to be clear and concrete and achieve the intent of the Constitution of the Kingdom of Thailand. The research suggests that the rule of law be enacted in the State Administration Act, B.E. 2534 (2000) by preparing a draft law on the administration of state affairs (No. ..) B.E. .... from research to enact a law under the legislative process for further enforcement. keywords : The Rule of Law, cabinet, The Government Authority, Development